Mentoring, educational services, and economic incentives: Longer-term evidence on risky behaviors from a randomized trial - Núria Rodríguez-Planas (Institute for the Study of Labor (IZA), 2010)
This paper is the first to use a randomized trial in the US to analyze the short- and long-term impacts of an after-school program that offered disadvantaged high-school youth: mentoring, educational services, and financial rewards to attend program activities, complete high-school and enroll in post-secondary education on youths' engagement in risky behaviors, such as substance abuse, criminal activity, and teenage childbearing. Outcomes were measured at three different points in time, when youths were in their late-teens, and when they were in their early- and their late-twenties. Overall the program was unsuccessful at reducing risky behaviors. Heterogeneity matters in that perverse effects are concentrated among certain subgroups, such as males, older youths, and youths from sites where youths received higher amount of stipends. We claim that this evidence is consistent with different models of youths' behavioral response to economic incentives. In addition, beneficial effects found in those sites in which QOP youths represented a large fraction of the entering class of 9th graders provides hope for these type of programs when operated in small communities and supports the hypothesis of peer effects.
Keywords: C93; I21; I22; I28; J24; 330; After-school program; short-; medium- and long-term effects; behavioral models; peer effects; criminal activity; teen childbearing and substance abuse; Jugendpolitik; Bildungspolitik; Ausbildungsfinanzierung; Wirkungsanalyse; Jugendliche; Randgruppe; Soziale Gruppe; USA